2020
DOI: 10.1007/s11244-020-01273-4
|View full text |Cite
|
Sign up to set email alerts
|

Cu–Fe Incorporated Graphene-Oxide Nanocomposite as Highly Efficient Catalyst in the Degradation of Dichlorodiphenyltrichloroethane (DDT) from Aqueous Solution

Abstract: Fe/graphene oxide and Cu–Fe/graphene oxide nanocomposite were synthesized by the atomic implantation method to study the photocatalytic degradation of dichlorodiphenyltrichloroethane (DDT). The synthesized nanocomposites were characterized by the XRD, N2 isotherms, SEM with EDX, TEM and XPS analysis. Characterization results have reported that oxides of Cu and Fe were uniformly distributed on graphene oxide and exited in the form of Cu+ and Fe2+ ions in Cu–Fe/graphene oxide nanocomposite. The high photocatalyt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(1 citation statement)
references
References 41 publications
(44 reference statements)
0
1
0
Order By: Relevance
“…It was observed that oxides of Cu and Fe were distributed equally on GO and were present as Cu + and Fe 2+ ions in the Cu–Fe/GO nanocomposite. Compared to Fe/GO, Cu–Fe/GO nanocomposites exhibited high photocatalytic DDT removal, reaching 99.7% at 0.2 g/L catalysts, 15 mg/L H 2 O 2 , and pH 5 through the generation of −OH radicals, which improved the DDT elimination ability [ 82 ].…”
Section: Applications Of Go and Rgomentioning
confidence: 99%
“…It was observed that oxides of Cu and Fe were distributed equally on GO and were present as Cu + and Fe 2+ ions in the Cu–Fe/GO nanocomposite. Compared to Fe/GO, Cu–Fe/GO nanocomposites exhibited high photocatalytic DDT removal, reaching 99.7% at 0.2 g/L catalysts, 15 mg/L H 2 O 2 , and pH 5 through the generation of −OH radicals, which improved the DDT elimination ability [ 82 ].…”
Section: Applications Of Go and Rgomentioning
confidence: 99%